1998
DOI: 10.1007/s001140050538
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Biomarkers and Straight-Chain Biopolymers in Humin: Implication for the Origin of Soil Organic Matter

Abstract: Soil organic matter is a very complex mixture of compounds derived from the decay of living organisms such as plants, fungi and bacteria. The mechanisms that control the preservation of soil organic matter are poorly known. This is notably due to our scarce knowledge of the molecular structure of humin, the insoluble part of soil organic matter. Three major hypotheses have been proposed to explain the formation of soil organic matter: the plant alteration hypothesis, the microbial synthesis hypothesis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…Depending on the research question, this may pose a problem; for instance, it might obscure chronology when molecules are used as proxies to reconstruct changes over time. Lichtfouse et al (1998b) showed that straight-chain lipids can become encapsulated in larger organic macromolecules, thus being protected against degradation. In addition, physical protection in (the micropores of) aggregates and/or through association with clay minerals has been identified as an important pathway for the stabilization of soil organic matter in general, including molecules used as molecular proxies (Tonneijck et al, 2010).…”
Section: Differences Between Different Soil Compartmentsmentioning
confidence: 99%
“…Depending on the research question, this may pose a problem; for instance, it might obscure chronology when molecules are used as proxies to reconstruct changes over time. Lichtfouse et al (1998b) showed that straight-chain lipids can become encapsulated in larger organic macromolecules, thus being protected against degradation. In addition, physical protection in (the micropores of) aggregates and/or through association with clay minerals has been identified as an important pathway for the stabilization of soil organic matter in general, including molecules used as molecular proxies (Tonneijck et al, 2010).…”
Section: Differences Between Different Soil Compartmentsmentioning
confidence: 99%
“…Il maggior sequestro di C si verifica nelle tesi in cui il materiale labile è associato ai materiali umificati caratterizzati dalla maggiore idrofobicità, confermando che l'uso di sostanze umiche stabilizzate potrebbe ritardare la decomposizione di tutto il pool di C del suolo (Whiteley e Pettit, 1994). Questa interpretazione è in accordo con altri studi che indicano le parti idrofiliche arricchite in gruppi alcolici come le più sensibili alla decomposizione e alle pratiche agronomiche (Wander e Traina, 1996;Almendros e Dorado, 1999;Zalba e Quiroga, 1999), mentre i pools più resistenti alla degradazione sono quelli derivanti da una preservazione selettiva dei biopolimeri con carattere più apolare, prevalentemente di natura alchilica (Almendros et al, 1996;Hatcher e Clifford, 1997;Lichtfouse et al, 1998;Spaccini et al, 2000;Cerli et al, 2008).…”
Section: La Perdita DI Sostanza Organica Del Suolounclassified
“…Resistant aliphatic biopolymer showing typical very thin laminae (25 µm thick) were indeed present [4], thus strengthening the biopolymer hypothesis. Further pyrolysis of humin followed by gas chromatography coupled to mass spectrometry (GC-MS) revealed the occurrence of C 11 -C 24 linear alkanes and alkene doublets [5,6] which are typical breakdown products of aliphatic biopolymers [3]. Therefore, a part of soil organic matter is indeed composed of straight-chain biopolymers (Fig.…”
Section: Resistant Straight-chain Biopolymersmentioning
confidence: 99%
“…Gas chromatography-mass spectrometric analysis of the humin pyrolysate revealed the occurrence of hopanoid and steroid biomarkers [6]. Biomarkers have been widely used to assess the biological sources of dead matter [12].…”
Section: Biomarkers In Huminmentioning
confidence: 99%